OPTIMASI WAKTU MASERASI PARASETAMOL DALAM JAMU PEGAL LINU YANG BEREDAR DI BOGOR BARAT - Bina Lohita Sari; Harry Noviardi; Nur Apriani Kartini (Jurnal Farmamedika (Pharmamedika Journal), 2017)
Jamu is a traditional medicine that is consumed by people.One type of herbal medicine on the market is Jamu Pegal Linu. Indonesian Govermment’s rule that this traditional medicine may not contain any synthetic chemical substance or drug functioned isolated compound. In reality there are still found some jamu pegal linu that contain medicine compound especially paracetamol. Analyzis chemical of drugs in herbal medicine has not been accompanied by the optimum times extraction. The aim of research to optimize of the time maceration and determine the contained of paracetamol in jamu pegal linu had circulated in Bogor Barat. Sample was taken by purposive sampling. Maceration from samples were using ethanol were within varying. Analysis of thin layer chromatography was using silica gel GF254 as the stationary phase, chloroform:ethanol (9:1) as the mobile phase with short waved UV as detection method. The results showed that 7 samples contained paracetamol from 10 samples of jamu pegal linu. The optimum of the time maceration between 0-30 minutes for herbal optimum simulation, sample D, F and S with a concentration of 2,49 to 22,33 %. The optimum of the time maceration between 60-90 minutes for the sample A, E and Q with levels of 4,47 to 7,12 %. Sample H had the optimum maceration time for 120 minutes with a concentration of 18.38%. Optimization of sample maceration time is dominated by the span of time between 30-90 minutes. Therefore, it is known that the samples of jamu pegal linu spread had maceration on the optimal time period between 30-90 minutes.